The evaluation of the predictors of left ventricular systolic function improvement in patients with severe aortic stenosis after aortic valve replacement - N.V. Ponych; O.J. Zharinov; O.A. Yepanchintseva; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate clinical and echocardiographic predictors of the systolic function improvement in patients with aortic stenosis (AS) and low left ventricular ejection fraction (LVEF) after aortic valve replacement (AVR). Material and methods. One-center study analyzed data received at clinical and instrumental examination of 72 consecutively examined patients with severe aortic stenosis and systolic dysfunction (LVEF less than 45 %) selected for AVR with or without coronary artery bypass grafting (CABG). The average age of patients was 62 (lower-upper quartiles 34–79) years. All patients underwent clinical and instrumental investigations, including transthoracic echocardiography and coronary angiography. Patients were retrospectively divided into two groups: 48 (66.76 %) patients with left ventricular ejection fraction increased more than 30 % in the early post-surgery period, and 24 (33.3 %) – less than 30 %. In 21 (29.2 %) patients AVR was combined with CABG.